2007
DOI: 10.1590/s0036-36342007000900012
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia en México de la infección y el estado de portador de la hepatitis B en adultos

Abstract: Objective. To estimate the prevalence of chronic hepatitis B infection and carrier status in Mexico; to analyze the frequency and distribution of hepatitis B markers in relation to the demographic and geographic variables and to identify risk factors. Materials and Methods. A total of 12 014 sera samples from the 2000 National Health Survey that were randomly selected for Anti-HB c and HBsAg were studied. The sera were collected between November 1999 and June 2000 on a national level. Results. Seroprevalence f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 15 publications
1
19
0
1
Order By: Relevance
“…In Mexico the prevalence of this marker has been reported at 0.14% (95%CI 0.05-0.27) in the age group of 20-29 y old (general population, not limited to health-related students or personnel). 8 Our students had similar HBsAg prevalence to that reported in Brazilian medical students 0.5%, 19 and different to that reported in Colombian and Taiwanese medical students at 0.15% and 1.7%, respectively. 27,28 Overall anti-HBc prevalence in our study was 1.0% (95%CI 0.87-1.13).…”
Section: Discussionsupporting
confidence: 48%
See 4 more Smart Citations
“…In Mexico the prevalence of this marker has been reported at 0.14% (95%CI 0.05-0.27) in the age group of 20-29 y old (general population, not limited to health-related students or personnel). 8 Our students had similar HBsAg prevalence to that reported in Brazilian medical students 0.5%, 19 and different to that reported in Colombian and Taiwanese medical students at 0.15% and 1.7%, respectively. 27,28 Overall anti-HBc prevalence in our study was 1.0% (95%CI 0.87-1.13).…”
Section: Discussionsupporting
confidence: 48%
“…This may be explained because the mean age in our study was 20 y and a positive correlation between age and detection of anti-HBc has been reported that it is doubled starting at 25 y in Mexico. 8,29 Thus our subjects may still be young to detected correlation between sexual activity and anti-HBc positivity. Risk factors such as male gender and being exposed to patients in clinical practice were not significantly associated with anti-HBc positivity (Table 4).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations